William F. Cody and Winifred Cody, 1958 (1958)
William F. Cody and Winnie Cody on the deck of a ship bound for Hawaii in 1958. Handwriting on back reads "Wini + Bill Cody 1958 on board of Fairline Ship on way to Hawaii".